LITERATUR REVIEW:PENGARUH POLA MAKAN DAN KURANGNYA AKTIVITAS FISIK TERHADAP TERJADINYA OBESITAS - Indah Risky Siregar (Jurnal Kesehatan, 2023)
Obesity is a disease associated with excess fat increasing the risk of health problems. Obesity is often caused by the intake of more calories than are consumed by exercise and the usual activities of daily living. The problem of being overweight or obese arises when we eat more high-calorie and fatty foods than this amount is needed. Calories that are not converted into energy and not used are stored as fat, causing obesity. Oil Coupled with unhealthy eating habits and an inactive body are also factors in obesity development. Obesity is also a very common problem in Indonesia. Obesity is a nutritional problem that has recently grown rapidly in both the upper and upper middle class.